THE ROLE OF ROOT PLANT ARCHITECTURE IN LANDSLIDE AND EROSION DISASTER MITIGATION - Sittadewi, Euthalia Hanggari; Tejakusuma, Iwan Gunawan (Jurnal Sains dan Teknologi Mitigasi Bencana, 2019)
Landslide and erosion disasters are become increasingly common in the last decade which resulted in financial losses and even human casualties. Therefore, disaster mitigation efforts of landslide and erosion are very important to be done immediately. A breakthrough of comprehensive and practical solution is highly expected for mitigation. Vegetation can improve slope stability, provide positive aspects for the environment, and provide mechanical and hydrological effects on slopes that are prone to landslide and erosion. The use of vegetation to mitigate landslide and erosion disasters is very potential to be developed because besides being effective, it is also economical and environmentally friendly. The mechanical aspects of plant roots is able to strengthen the soil. Plant root characteristics such as root architecture, root anchor index (IJA), root grip index (ICA) are important variables to determine the types of plants that will be used in mitigating landslide and erosion.